DIETARY COMPLIANCE AND WOUND CONDITION IN DIABETIC ULCER PATIENTS - Kurniasaria, Intan Endyka; Faridah, Umi; Jauhar, Muhamad; Pusparatri, Edita (Universitas Muhammadiyah Kudus, 2025)
Diabetic ulcers are a complication in patients with uncontrolled diabetes mellitus. Patients with diabetic ulcers feel anxious and burdened economically, socially, and medically. There is an increasing number of diabetic ulcer cases in hospitals globally and nationally. Seeing this fact, it is necessary to know factors that can accelerate wound healing such as diet, medication, and physical activity. The purpose of this study was to analyze the relationship between dietary compliance and wound conditions in diabetic ulcer patients. This study was a quantitative study, correlation analysis with a cross-sectional approach. The independent variable was dietary compliance. The dependent variable was the wound condition of diabetic ulcer patients. The study was conducted at Dr. Rehatta Regional General Hospital in June-July 2025. A total of 66 samples were selected through a purposive sampling technique. 66 samples were obtained using the Slovin formula. The inclusion criteria were patients diagnosed with diabetes mellitus, diabetic ulcer wounds, composmentis, surgical poly patients, able to read or hear and answer questions on the questionnaire. The exclusion criteria were patients with other disease complications. The research instrument used a dietary compliance questionnaire and a Bates Jensen wound assessment tool observation sheet. Data analysis used the Spearman Rho correlation test. The Spearman Rho test results showed a value (p = 0.000; p 0.05). It was concluded that there was a significant relationship between dietary compliance and wound conditions in diabetic ulcer patients. The correlation coefficient value showed a positive correlation direction with a strong category. It is expected that patients with diabetic ulcers can improve compliance in implementing the recommended dietary pattern.Hospitals are expected to always provide motivation and education to diabetes sufferers regarding diabetes, through service activities inside and outside the building such as posbindu, posyandu and home visits.